BUDAYA INDONESIA DALAM MOCKUMENTARY â€œMALAM MINGGU MIKO 2â€ KOMPAS TV - Rohma, Naafi Nur; Sjafiâ€™i, Achmad (Seni Media Rekam ISI Surakarta, 2017)
The serial program of comedy â€œMalam Minggu Miko 2â€ the story of â€˜Malam Baru Mikoâ€™ which is broadcasted by Kompas TV is a program which shows in mockumentary format. It is a format of television broadcasting program which contains of fictive story filmed similarly to documentary format that its roles have realistic characters and reflect current real life. This study considers television device as a text. Employing semiotic approach of Charles Sanders Peirce, relating three main components: representamen, object, and interpretant. This study investigates the significances of Indonesian cultural marks emerged on the text. Limitation of the Indonesian cultural marks emerged includes politeness, regards, greetings, smiles, respects, hospitalities, gotong royong (mutual helps), and slametan (traditional feast). The result of this study shows that some marks considered as Indonesian culture are found in some frames of pictures from the serial program of comedy â€œMalam Minggu Miko 2â€ the story of â€˜Malam Baru Mikoâ€™ broadcasted by Kompas TV.Â Keywords: Culture, Indonesia, mockumentary, and semiotics